Hafiz and difamiliarization in allusioms - حمیدرضا توکلی (مطالعات زبانی و بلاغی)
Allusion (Talmih) is a usual and ancient rhetorical âtechnique in literature of Iran and the world. In this article, âHafiz's approach to fictional allusions is studied. Hafiz âreconstructs celebrated allusions into different and essentric âstyles .Hafiz frequently considers stories in a different way, âor uses amphiboly and symmetry to do complex indicational âand accociational structure of allusion. He further mixes âdifferent traditions with reference to their allusions.â